Domestic Violence in the Northeast: an analysis of the Information System for Diseases and Notification (SINAN) data between 2009 and 2018 (Research, Society and Development, 2021)
Domestic and family violence against women is defined and legally supported by the Maria da Penha Law (Law nº11340, of August 7, 2006). It is common for this type of violence to be practiced by partner and feminicide, the most serious of these crimes, has a high prevalence in Brazil. According to WHO data, in Brazil’s Northeast the region with the biggest amount of cases is the Zona da Mata in Pernambuco. The aim of this work is to characterize the profile of domestic violence in the Northeast using the data obtained by the compulsory notification at Information System for Diseases and Notification (SINAN) between 2009 and 2018. The study is observational and data gathering took place between May and July 2020 through the selection of variables from the Compulsory Notification Form of Domestic, Sexual and Other Interpersonal Violence. During this period, 180,555 cases of domestic violence were reported in the Northeast. The highest number of notifications occurred in 2018 with 31,268 cases. The predominant type was physical violence, with 122,684 cases, followed by psychological/moral violence with 58,321 cases. The perpetrator of the aggression was the husband in 21.81% of the cases, 45.56% corresponding to aggression by physical force/beating.